A Case with Down Syndrome Who Developed Pericardial Tamponade due to COVID-19 - Hatice Yıldız; Servet Ergün; Mutlu Uysal Yazıcı; Fatma Nur Öz; Naci Ceviz (Galenos Yayinevi, 2021)
Cardiac tamponade is a life-threatening condition that disrupts normal hemodynamics, limits the adequate filling of the heart cavities, and occurs with sudden and/or excessive fluid accumulation in the pericardial cavity. Cardiac tamponade is rare in pediatric patients and requires early diagnosis and urgent intervention. Herein, we present an 11-month-old boy with Down syndrome who developed pericardial tamponade associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and acute respiratory distress syndrome. An 11-month-old boy with Down syndrome was admitted to the pediatric infection service due to cough and respiratory distress. Pericardial effusion was detected in the follow-up of the patient whose SARS-CoV-2 polymerase chain reaction test was positive. Ibuprofen treatment was started for pericardial effusion. During the follow-up, the patient who developed respiratory distress was transferred to the intensive care unit, intubated and mechanically ventilated. In the intensive care unit, the patient developed hypotension and cardiac tamponade. An emergency pericardiocentesis was performed. Despite pericardiocentesis, the patient's hypotension persisted. The patient died due to acute respiratory distress syndrome. Coexistence of cardiac tamponade and Coronavirus disease-2019 (COVID-19) in children has been rarely reported. We do not have enough knowledge about the course of COVID-19 in patients with Down syndrome. This case is presented in order to ensure the early recognition of similar cases in the SARSCoV- 2 pandemic and to be more careful in ARDS due to COVID-19 infection in patients with Down syndrome.